THE CREATIVE LEGACY OF THE TOGYZTARAU KUY MASTER MUSA TEKESBAYULY1 - Yernat Zhamanbalinov (Theoretical Hypotheses and Empirical Results, 2025)
In 2020, within the framework of the program “Seven facets of the Great Steppe” initiated by the First President of the Republic of Kazakhstan, Nursultan Nazarbayev, the second volume of the three-volume anthology “Ancient Motifs of the Great Steppe” entitled “Ancient instrumental motifs. Traditional kuy art” [1] was published under the editorship of Associate Professor, Candidate of Arts Ainur Kaztuganova,. This publication became one of the most significant events in contemporary Kazakh kuyshi studies. The anthology, which encompasses the kuy traditions of all regions of Kazakhstan, including local and individual schools, is remarkable for presenting not only selected works of classical kuyshi-composers but also for including names and pieces of performers that had never appeared in print before. Among the most striking examples are the second variant of Kurmangazy’s “Saryarka”, “Eski bulbul”, and the second version of Zhantore’s famous “Shalkyma”. The publication of this anthology became possible thanks to the selection and systematization of numerous kuy recordings made during various expeditions of the M.O. Auezov Institute of Literature and Art, which had been deposited in its manuscript archive. In addition, through direct collaboration with regional kuyshis, the anthology also incorporated rarely performed or previously unknown kuys from their repertoires. Importantly, the newly introduced pieces represent all traditional schools.